Sodium storage and capacity retention behavior derived from high-spin/low-spin Fe redox reaction in monoclinic Prussian blue based on operando Mössbauer characterization. (May 2023) - Wang, Zinan; Sougrati, Moulay Tahar; He, Yawen; Le Pham, Phuong Nam; Xu, Wei; Iadecola, Antonella; Ge, Rile; Zhou, Wenhui; Zheng, Qiong; Li, Xianfeng; Wang, Junhu
Abstract: Owing to the high theoretical specific capacity, long cycle life, abundant resources and environmental benignity, iron-based Prussian blue analogues (PBAs) as cathode materials for sodium-ion batteries (SIBs) have been investigated widely in recent years. Although major efforts have been concentrated on exploitation of high performance's PBAs cathode materials, there is still deficiency of a deep understanding of the relevance between the reaction processes and capacity degradation mechanism with the active high-spin (HS)/ low-spin (LS) iron sites, which is of great significance. In this work, well-crystallized and shape-controlled monoclinic Prussian blue (M-PB) was successfully prepared, with remarkable electrochemical performance, especially in cycling performance (88% capacity retention after 500 cycles at 120 mAh g −1, and 81% after 980 cycles). More significantly, with state-of-the-art operando Mössbauer spectroscopy, ex-situ 77 K Mössbauer spectroscopy, ex-situ X-ray absorption spectroscopy and operando X-ray diffraction, the reaction and capacity degradation mechanism were investigated thoroughly and the detailed reaction process was figured out for the first time. The result showed clearly that the HS Fe in M-PB reacts completely and contributes to most capacity, while only part of LS Fe reacts. Therefore, the capacity enhancement should be achieved by activating LS Fe. Furthermore, the LS Fe (Fe-CN) results in more severe crystal structure change than HS Fe (Fe-NC) of the same amount in the electrochemical reaction process, thus the partial reaction of LS Fe in M-PB could be the reason for its excellent cycling performance. This work not only investigated the reaction and capacity degradation mechanism, but also shed light on the design of high-performance PBAs-based cathodes for SIBs. Graphical Abstract: The reaction and capacity degradation of Prussian blue-based cathode was related to high-spin/low-spin Fe redox in sodium-ion batteries through operando techniques. ga1 Highlights: Monoclinic Prussian Blue as cathode materials shew competitive performance. Operando Mössbauer spectroscopy was first utilized for Prussian blue analogues. High-spin Fe and low-spin Fe reacted stepwise, high-spin iron reacted most. Low-spin Fe led to more severe crystal structure change than high-spin Fe.